The emerging role of microtubules in invasion plasticity - Legátová, Anna; Pelantová, Markéta; Rösel, Daniel; Brábek, Jan; Škarková, Aneta (Frontiers in Oncology, 2023)
The ability of cells to switch between different invasive modes during metastasis, also known as invasion plasticity, is an important characteristic of tumor cells that makes them able to resist treatment targeted to a particular invasion mode. Due to the rapid changes in cell morphology during the transition between mesenchymal and amoeboid invasion, it is evident that this process requires remodeling of the cytoskeleton. Although the role of the actin cytoskeleton in cell invasion and plasticity is already quite well described, the contribution of microtubules is not yet fully clarified. It is not easy to infer whether destabilization of microtubules leads to higher invasiveness or the opposite since the complex microtubular network acts differently in diverse invasive modes. While mesenchymal migration typically requires microtubules at the leading edge of migrating cells to stabilize protrusions and form adhesive structures, amoeboid invasion is possible even in the absence of long, stable microtubules, albeit there are also cases of amoeboid cells where microtubules contribute to effective migration. Moreover, complex crosstalk of microtubules with other cytoskeletal networks participates in invasion regulation. Altogether, microtubules play an important role in tumor cell plasticity and can be therefore targeted to affect not only cell proliferation but also invasive properties of migrating cells.